The Fourth Dialog State Tracking Challenge - Kim, Seokhwan; D'Haro, Luis Fernando; Banchs, Rafael E.; Williams, Jason; Henderson, Matthew (Proceedings International Workshop on Spoken Dialog Systems (IWSDS), 2016)
Dialog state tracking is one of the key sub-tasks of dialog management, which defines the representation of dialog states and updates them at each moment on a given on-going conversation. To provide a common test bed for this task, three dialog state tracking challenges have been completed. In this fourth challenge, we focused on dialog state tracking on human-human dialogs. The challenge received a total of 24 entries from 7 research groups. Most of the submitted entries outperformed the baseline tracker based on string matching with ontology contents. Moreover, further significant improvements in tracking performances were achieved by combining the results from multiple trackers. In addition to the main task, we also conducted pilot track evaluations for other core components in developing modular dialog systems using the same dataset.